Violence Received, Exerted and Perceived Questionnaire revised version (VREP-R): Psychometric Properties in Cuban University Students - Ramos Rangel, Yamila (2024)
The availability of adequate instruments that measure dating violence is essential in Cuba to strengthen the evidence and support preventive actions with effective diagnoses. The objective of the research was to analyze psychometric properties of the Revised Received, Exerted, and Perceived Violence Questionnaire (VREP-R) in its Cuban version. An instrumental design study, specifically psychometric, was carried out with the participation of 356 students aged 18 to 24 from the University of Medical Sciences of Cienfuegos. In the confirmatory factor analysis of the scale, the adjusted model showed an excellent fit index, with an RMSEA of .050. Furthermore, the CFI indicated a good fit, obtaining a value of .969. The instrument was reduced to 22 items, preserving the five original factors, which explained 65.684% of the accumulated variation. The scale is confirmed multidimensional, with indicators appropriately related to its dimensions. Adequate reliability values were obtained through internal consistency (α =.94 and ω =.90). The temporal stability of the measure was assessed using Spearman's assessment between measurements at two different times. A substantial evaluation was found between the measurements at the first and second moments; statistics ranged between .50. and .95. It is concluded that the VREP-R is a brief, adequate, easy-to-apply measurement instrument that meets the psychometric requirements, being reliable and valid to measure dating violence received, exercised and perceived, aspect non-existent until now in Cuba.